Pesan Moral Gerakan Palembang Peduli Hewan Dalam Meningkatkan Kepedulian Masyarakat Terhadap Kucing Liar Di Palembang - Maharani, Ayu; Hamandia, Muhammad Randicha; Nuraida, Nuraida (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "The Moral Message of the Palembang Animal Care Movement in Raising Public Concern for Feral Cats in Palembang". Cats are the closest animals to humans. In Islam the Prophet Muhammad SAW loved cats so much. He advised Muslims to keep cats and treat cats as members of his family and take good care of them. The Prophet Muhammad taught us to love all creatures on this earth. Showing compassion towards animals is part of faith in Islam. The number of cases of violence experienced by cats by some people shows that inequality against cats is still often found, due to the lack of public attention to the welfare of cats. Along with the times, all forms of crimes against animals, one of which is cats. Cats become animals that experience acts of violence in the form of acts of persecution committed by humans intentionally. The formulation of the problem in this study is How is the moral message of the Palembang Animal Care Movement in raising public awareness of stray cats in Palembang and What moral values are contained in the Palembang Animal Care Movement in raising public awareness of stray cats in Palembang. This research uses a qualitative approach. The data collection techniques were field observation, in-depth interviews and documentation in the form of photographs. The theory used in this research is social construction theory proposed by Peter L Beger The term social construction of reality is defined as a social process through actions and interactions in which individuals create continuously a reality that is owned and experienced together subjectively through externalization, objectivation, and internalization. The research results of this study are that there are 5 moral messages contained, namely helping each other fellow living things not only to humans, do good to animals. Never hurt them, it is not a loss to share food with stray cats, continue to care for wild animals wherever they are and continue to do the best for stray cats. And there are 6 moral values contained, namely mercy, patience, compassion, empathy, helping and social action.